Understanding the Experiences of Black Women Medical Students and Residents: A Narrative Review - Sharp, Sacha; Hixson, Ashley; Stumpff, Julia; Williamson, Francesca (Frontiers in Public Health, 2022)
Background: Few research studies examine medical students and residents with intersectional identities. In the emerging literature, data on Black women’s experiences may be misrepresented and misinterpreted as studies aggregate data for women, students of color, and Black/African American men. As such, these studies do not account for the nuanced experiences of gendered racism that Black women students and residents may encounter during their medical education. Methods: Using Crenshaw’s intersectionality as an analytical tool, we conducted a narrative review to highlight how Black women medical students and residents are rendered invisible in the current literature on medical education. Results: The results generated 13 citations specifically discussing Black women medical students and residents, with only six studies being empirical research. Conclusion: We conclude that 13 articles is inadequate for understanding the experiences of these populations. Without centering Black women or using an intersectional lens, researchers could invalidate the lived experiences of this population and create barriers to the political resources Black women learners need to be successful. Moreover, the lack of intention behind addressing the needs of Black women can be viewed as complicity in the oppressive structures that serve to subjugate them.